Anti-leishmanial activity of Carthamus tinctorius and Matricaria chamomilla extracts on the survival of promastigotes of Leishmania major - S Hamoonnavard; H Rezvan; M Maleki; H Heydarianpour; B Bazargani-Gilani; F Behdarvand (Armaghane Danesh Bimonthly Journal)
1.Jabini R, Jaafari M, Hasani FV, Ghazizadeh F, Khamesipour A, Karimi G. Effects of combined therapy with silymarin and glucantime on leishmaniasis induced by Leishmania major in BALB/c mice. Drug Research 2015; 65(03): 119-24. ## 2.Diro E, Lynen L, Mohammed R, Boelaert M, Hailu A, van Griensven J. High parasitological failure rate of visceral leishmaniasis to sodium stibogluconate among HIV co-infected adults in Ethiopia. PLoS Neglected Tropical Diseases 2014; 8(5): e2875. ## 3.Machado M, Pires P, Dinis A, Santos-Rosa M, Alves V, Salgueiro L, et al. Monoterpenic aldehydes as potential anti-Leishmania agents: activity of Cymbopogon citratus and citral on L. infantum, L. tropica and L. major. Experimental Parasitology 2012; 130(3): 223-31. ## 4.Oryan A, Alidadi S, Akbari M. Risk factors associated with leishmaniasis. Trop Med Surg 2014; 2(3): e118. ## 5.Sifaoui I, López-Arencibia A, Martín-Navarro CM, Chammem N, Reyes-Batlle M, Mejri M, et al. Activity of olive leaf extracts against the promastigote stage of Leishmania species and their correlation with the antioxidant activity. Experimental Parasitology 2014; 141: 106-11. ## 6.Oryan A. Plant-derived compounds in treatment of leishmaniasis. Iranian Journal of Veterinary Research 2015; 16(1): 1. ## 7.Zhao G, Zheng X-W, Gai Y, Chu WJ, Qin GW, Guo LH. Safflower extracts functionally regulate monoamine transporters. Journal of Ethnopharmacology 2009; 124(1): 116-24. ## 8.Shirwaikar A, Khan S, Kamariya YH, Patel BD, Gajera FP. Medicinal plants for the management of post menopausal osteoporosis: A review. The Open Bone Journal 2010; 2(1): 1-13. ## 9.Singh V, Nimbkar N. Safflower(Carthamus tinctorius L.). Chapter 2006; 6: 167-94. ## 10.Zhou XiDan ZX, Tang LiYing TL, Xu YiLong XY, Zhou GuoHong ZG, Wang ZhuJu WZ. Towards a better understanding of medicinal uses of Carthamus tinctorius L. In Traditional Chinese Medicine: a Phytochemical and Pharmacological Review 2014; 151(1): 27-43. ## 11.Hiramatsu M, Takahashi T, Komatsu M, Kido T, Kasahara Y. Antioxidant and neuroprotective activities of Mogami-benibana (safflower, Carthamus tinctorius Linne). Neurochemical Research 2009; 34: 795-805. ## 12.Esmaeili S, Ghiaee A, Naghibi F, Mosaddegh M. Antiplasmodial activity and cytotoxicity of plants used in traditional medicine of Iran for the treatment of fever. Iranian Journal of Pharmaceutical Research: IJPR 2015; 14(Suppl): 103. ## 13.Singh O, Khanam Z, Misra N, Srivastava MK. Chamomile (Matricaria chamomilla L.): an overview. Pharmacognosy Reviews 2011; 5(9):82. ## 14.Živković J, Ilić M, Šavikin K, Zdunić G, Ilić A, Stojković D. Traditional use of medicinal plants in South-Eastern Serbia (Pčinja District): Ethnopharmacological investigation on the current status and comparison with half a century old data. Frontiers in Pharmacology 2020; 11: 1020. ## 15.Petrakou K, Iatrou G, Lamari FN. Ethnopharmacological survey of medicinal plants traded in herbal markets in the Peloponnisos, Greece. Journal of Herbal Medicine 2020; 19: 100305. ## 16.El Mihyaoui A, Esteves da Silva JC, Charfi S, Candela Castillo ME, Lamarti A, Arnao MB. Chamomile (Matricaria chamomilla L.): a review of ethnomedicinal use, phytochemistry and pharmacological uses. Life 2022; 12(4): 479. ## 17.Dashtpeima A, Moshfe A, Manzoori L, Arefkhah N, Shahryari S, Mohseni M, et al. The Effect (s) of Matricaria chamomilla on Leishmania major Ulcers in Balb/c Mice. Armaghane Danesh 2015; 20(2): 127-37. ## 18.Zargari A, Mazandarani M, Hoseini S. Effect of safflower(Carthamus tinctorius) extract on the nonspecific immune system of rainbow trout. Oncorhynchus Mykiss(Walbaum, 1792) 2020; 7(4):118-32. ## 19.Costescu CI, Hadaruga N, Rivis A, Hadaruga D, Lupea A, Pârvu D. Antioxidant activity evaluation of some Matricaria chamomilla L. extracts. Journal of Agroalimentary Processes and Technologies 2008; 14(2): 417-32. ## 20.Farahani MK, Bitaraf FS, Atashi A, Jabbarpour Z. Evaluation of anticancer effects of frankincense on breast cancer stem‐like cells. Cancer Reports 2023; 6(2): e1693. ## 21.Akbari M, Oryan A, Hatam G. Application of nanotechnology in treatment of leishmaniasis: a review. Acta Tropica 2017; 1(172): 86-90. ## 22.Salem MM, Werbovetz KA. Natural products from plants as drug candidates and lead compounds against leishmaniasis and trypanosomiasis. Current Medicinal Chemistry 2006; 13(21): 2571–98. ## 23.Hassan AA, Khalid HE, Abdalla AH, Mukhtar MM, Osman WJ, Efferth T. Antileishmanial activities of medicinal herbs and phytochemicals in vitro and in vivo: An update for the years 2015 to 2021. Molecules 2022; 27(21): 7579. ## 24.Zadeh Mehrizi T, Pirali Hamedani M, Ebrahimi Shahmabadi H, Mirzaei M, Shafiee Ardestani M, Haji Molla Hoseini M, et al. Effective materials of medicinal plants for leishmania treatment in vivo environment. Journal of Medicinal Plants 2020; 19(74): 39-62. ## 25.Rezvan H, Ali SA, Navard SH, Rees R. Evaluation of murine OX40L-murine IgG1(MM1) fusion protein on immunogenicity against L. mexicana infection in BALB/c mice. Comparative Immunology, Microbiology and Infectious Diseases 2023; 99: 102011,1-5. ## 26.Hamoon Navard SH, Rezvan H, Haddad MHF, Ali S, Nourian A, Eslaminejad MB, et al. Therapeutic effects of mesenchymal stem cells on cutaneous leishmaniasis lesions caused by Leishmania major. Journal of Global Antimicrobial Resistance 2020; 23: 243-50. ## 27.Hamoon Navard S, Rezvan H, Feiz Haddad MH, Baghaban Eslaminejad M, Azami S. Expression of cytokine genes in Leishmania major-infected BALB/c mice treated with mesenchymal stem cells. Journal of Medical Microbiology and Infectious Diseases 2020; 8(1): 7-13. ## 28.Hussain AY, Hussein HJ, Al-Rubaye AF. Antifungal Activity of the Secondary Metabolites Extracted. Clin Schizophr Relat Psychoses 2021; 15(6): 1-6. ## 29.Harsh M, Nag T. Flavonoids with antimicrobial activities of arid zone plants. Geobios, India,  1988; 15(1); 32-5. ## 30.Kermanshahi K, Moater F, Soleimani Manesh A. Evaluation of the antibacterial effects of aqueous and ethanolic extracts of safflower on a bacteria. Journal of the Faculty of Science of Shahid chamran University  2006; 15: 18-26. ## 31.Karimkhani M, Shaddel R, Khodaparast M, Vazirian M, Piri-Gheshlaghi S. Antioxidant and antibacterial activity of safflower (Carthamus tinctorius L.) extract from four different cultivars. Quality Assurance and Safety of Crops & Foods 2016; 8(4): 565-74. ## 32.Dobrin A, Popa G. Evaluation of the antimicrobial activity of Carthamus tinctorius extracts against nosocomial microorganisms. Scientific Papers Series B Horticulture 2022; 66(1): 799-806. ## 33.Haleem AM, Hameed A, Al-Majeed RA, Hussein NN, Hikmat RA, Queen BK, editors. Anticancer, Antioxidant, Antimicrobial and Cytogenetic Effects of Ethanol Leaves Extract of Carthamus tinctorius. IOP Conference Series: Earth and Environmental Science; 2023: IOP Publishing. 4th International Conference of Modern Technologies in Agricultural Sciences. ## 34.Stanojevic LP, Marjanovic-Balaban ZR, Kalaba VD, Stanojevic JS, Cvetkovic DJ. Chemical composition, antioxidant and antimicrobial activity of chamomile flowers essential oil (Matricaria chamomilla L.). Journal of Essential Oil Bearing Plants 2016; 19(8): 2017-28. ## 35.Akram W, Ahmed S, Rihan M, Arora S, Khalid M, Ahmad S, et al. An updated comprehensive review of the therapeutic properties of Chamomile (Matricaria chamomilla L.). International Journal of Food Properties 2024; 27(1): 133-64. ## 36.Hajaji S, Sifaoui I, López-Arencibia A, Reyes-Batlle M, Jiménez IA, Bazzocchi IL, et al. Leishmanicidal activity of α-bisabolol from Tunisian chamomile essential oil. Parasitology Research 2018; 117: 2855–67. ## 37.Morales-Yuste M, Morillas-Márquez F, Martín-Sánchez J, Valero-López A, Navarro-Moll M. Activity of (-) α-bisabolol against Leishmania infantum promastigotes. Phytomedicine 2010; 17(3-4): 279–81. ## 38.Corpas-López V, Merino-Espinosa G, López-Viota M, Gijón-Robles P, Morillas-Mancilla MJ, López-Viota J, et al. Topical treatment of Leishmania tropica infection using (−)-α-bisabolol ointment in a hamster model: Effectiveness and safety assessment. Journal of Natural Products 2016; 79(9): 2403–7. ## 39.Cavalieri E, Mariotto S, Fabrizi C, de Prati AC, Gottardo R, Leone S, et al. α-Bisabolol, a nontoxic natural compound, strongly induces apoptosis in glioma cells. Biochemical and Biophysical Research Communications 2004; 315(3): 589–94. ## 40.Chen W, Hou J, Yin Y, Jang J, Zheng Z, Fan H, et al. α-Bisabolol induces dose-and time-pendent apoptosis in HepG2 cells via a Fas-and mitochondrial-related pathway, involves p53 and NFκB. Biochemical Pharmacology 2010; 80(2): 247–54. ##